Kontribusi Orang Tua dalam Pendidikan Karakter Anak pada Usia Sekolah Dasar - Cahyono, Dedi Dwi; Darsinah, Darsinah; Wulandari, Murfiah Dewi (MASALIQ, 2022)
Children's education begins with upbringing from their parents or family, if the education is good and attentive, the child will not be far from following the direction of education as ordered by his family. Parents are the main contribution in the formation of children's character because after that children will be educated in educational institutions and will grow up in their environment. The age of the child when entering elementary school is a period where the child has known his friends, this can affect the environment and can bring changes in human behavior to get new things, both negative and positive.